The Essential Aspects of Teaching Children to Read in English - Hartati Hartati; Siti Misra Susanti; Henny Henny; Asma Kurniati; Marwah Marwah (Hasanuddin University, 2021)
This paper aims to introduce the essential aspects that teachers should know in teaching children to read in English. The age level of the children referred to in this paper are children aged 5 to 7 years. The aspects include the characteristics of children, the importance of teaching children to read in English, decoding and phonemic awareness. The aspects were selected from the results of the analysis of previous related literature that are still considered important for discussion so as to provide new treasures for teachers in particular. With this paper, it is hoped that it can enrich information about teaching young chidren to read in English and increase the teacher's insight about teaching young children to read in English so that teaching reading can take place effectively.